Urban climate effects on extreme temperatures in Madison, Wisconsin, USA. (24th September 2015) - Schatz, Jason; Kucharik, Christopher J
Abstract: As climate change increases the frequency and intensity of extreme heat, cities and their urban heat island (UHI) effects are growing, as are the urban populations encountering them. These mutually reinforcing trends present a growing risk for urban populations. However, we have limited understanding of urban climates during extreme temperature episodes, when additional heat from the UHI may be most consequential. We observed a historically hot summer and historically cold winter using an array of up to 150 temperature and relative humidity sensors in and around Madison, Wisconsin, an urban area of population 402 000 surrounded by lakes and a rural landscape of agriculture, forests, wetlands, and grasslands. In the summer of 2012 (third hottest since 1869), Madison's urban areas experienced up to twice as many hours ⩾32.2 °C (90 °F), mean July T MAX up to 1.8 °C higher, and mean July T MIN up to 5.3 °C higher than rural areas. During a record setting heat wave, dense urban areas spent over four consecutive nights above the National Weather Service nighttime heat stress threshold of 26.7 °C (80 °F), while rural areas fell below 26.7 °C nearly every night. In the winter of 2013–14 (coldest in 35 years), Madison's most densely built urban areas experienced up to 40% fewer hours ⩽−17.8 °C (0 °F), mean January T MAX up to 1 °C higher, and mean January T MIN up to 3 °C higher than rural areas. Spatially, the UHI tended to be most intense in areas with higher population densities. Temporally, both daytime and nighttime UHIs tended to be slightly more intense during more-extreme heat days compared to average summer days. These results help us understand the climates for which cities must prepare in a warming, urbanizing world.